The effects of renal dysfunction on patients undergoing coronary artery bypass grafting in Hospital Universiti Sains Malaysia - Ahmad Zuhdi, Mamat (2010)
Chronic kidney disease (CKJD) has been known to be a potent risk factor for cardiovascular death. It has been implicated in the adverse outcomes seen in patients after their coronary artery bypass grafting (CABG). The aim of this study is to evaluate the relation between renal dysfunction and the morbidity and mortality following CABG. Hospital, Kubang Kerian were collected. These patients were divided into 2 groups, according to their estimated glomerular filtration rate (GFR) using the Cockcroft- Gault formula. Estimated GFR of less than 60 ml/min were grouped into the renal dysfunction, whilst GFR >60ml/min were grouped as non-renal dysfunction. These retrospective data were analysed for its demographic and outcomes after the procedure, including the short and long term mortality rates. Results: All the 215 records representing 215 patients were successfully collected and analysed. 117 (54.4%) patients had estimated GFR <60 ml/min and labelled as renal dysfunction group. This group of patient had a significantly lower body mass index, poorer pre-operative ejection fraction and was older. There were also more incidences of diabetes mellitus and hypertension within this group (p=0.005 and 0.031). Intra-operative data showed that the renal dysfunction group had shorter cross-clamp time (p=0.018) and used up less cardioplegia (p=0.004) during the bypass. Post-operative data analysis showed that the patients with renal dysfunction had more chance of developing acute renal failure (p<0.001) and arrhythmia (p=0.047). A total 10 patients who died within 30 days and 15 patients died within 3 years of CABG, but there was no significant difference noted between these 2 groups. Conclusion: This study supported the evidences that pre-operative renal dysfunction, acute renal failure and arrhythmia. The relation between renal dysfunction and postoperative mortalities was however failed to be demonstrated in this study, as compared to many other studies before.